Solid‐state reflective displays (SRD®) for video‐rate, full color, outdoor readable displays. Issue 10 (29th August 2018) - Talagrand, Clement; Triggs, Graham; Bandhu, Lokeshwar; Garcia‐Castillo, Sergio; Broughton, Ben; Bhaskaran, Harish; Hosseini, Peiman
Abstract: Solid‐state reflective displays (SRD ® ) have been proposed as a new route for next generation reflective displays. We present the first optical measurements of a combined RGBW states, together with a simulated black state. These results demonstrate the feasibility of a future high performance, video capable, full color, solid‐state reflective display. Abstract : Solid‐state reflective displays (SRD ® ) are proposed as a new route for next generation high performance reflective displays. We demonstrate for the first time a video capable technology with a total measured gamut of 61% sRGB and simultaneous luminance of L* = 68.975 (Y = 0.394).